2009
DOI: 10.1177/070674370905400708
|View full text |Cite
|
Sign up to set email alerts
|

General Practice and Mental Health Care: Determinants of Outpatient Service Use

Abstract: Objective: To examine the determinants that lead Canadian adults to consult family physicians, psychiatrists, psychologists, psychotherapists, and other health professionals for mental health reasons and to compare the determinants of service use across provider types. Method: Data from the Canadian Community Health Survey: Mental Health and Well-Being were used for people aged 18 years and older (n = 35 236). A multivariate logistic regression was used to model outpatient consultations with different provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
68
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 52 publications
13
68
1
7
Order By: Relevance
“…This finding is supported by previous studies showing that those without comorbid physical chronic conditions have fewer health care encounters and are therefore less likely to be diagnosed and treated for their mental health issues than those with them. 39,40 Regarding affected Canadians' health status, we found those with long delay were more likely to report the most (≥ 3) activity limitations and "poor" or "fair" mental health. Results from our supplemental analysis provided further confirmation of this, demonstrating that for every year increase in time to diagnosis there was a 5.0% and 4.0% increase in odds of having three or more activity limitations (relative to those with no activity limitations) and "poor" or "fair" mental health (relative to those with "very good" or "excellent" mental health), respectively, upon controlling for all other individual characteristics (data not shown; available upon request).…”
Section: Discussionmentioning
confidence: 85%
“…This finding is supported by previous studies showing that those without comorbid physical chronic conditions have fewer health care encounters and are therefore less likely to be diagnosed and treated for their mental health issues than those with them. 39,40 Regarding affected Canadians' health status, we found those with long delay were more likely to report the most (≥ 3) activity limitations and "poor" or "fair" mental health. Results from our supplemental analysis provided further confirmation of this, demonstrating that for every year increase in time to diagnosis there was a 5.0% and 4.0% increase in odds of having three or more activity limitations (relative to those with no activity limitations) and "poor" or "fair" mental health (relative to those with "very good" or "excellent" mental health), respectively, upon controlling for all other individual characteristics (data not shown; available upon request).…”
Section: Discussionmentioning
confidence: 85%
“…34 A study examining determinants that lead Canadian adults to consult family physicians, psychiatrists, psychologists, psychotherapists and other health professionals for mental health reasons found that those with lower levels of education and income adequacy were less likely to use mental health services, specifically specialty providers of psychotherapy. 35 Furthermore, a Canadian study that examined barriers to mental health care using data from the Canadian Community Health Survey concluded that "despite universal health insurance, there are significant inequi ties in access to mental health care for low-income Canadians." 36 been shown to exist 35,37 and results from our study might well reflect real regional differences.…”
Section: Discussionmentioning
confidence: 99%
“…Cette observation est étayée par des études antérieures mon trant que les personnes sans comorbidité physique avaient moins souvent recours aux services de soins de santé et, par conséquent, étaient moins nombreuses à recevoir un diagnostic de trouble de santé mentale et un traitement adapté que les personnes souffrant déjà d'une affection physique chronique 39,40 .…”
Section: Tableau 2 Association Entre Les Caractéristiques Sociodémogrunclassified